2020
DOI: 10.1016/j.jelectrocard.2020.10.015
|View full text |Cite
|
Sign up to set email alerts
|

The effect of favipiravir on QTc interval in patients hospitalized with coronavirus disease 2019

Abstract: Background The effect of favipiravir on the QTc interval during the treatment of Coronavirus Disease 2019 (COVID-19) patients is unclear. Thus, the current study objective was to evaluate any change in the QTc interval in patients who were hospitalized due to COVID-19 receiving favipiravir treatment. Method Patients hospitalized with COVID-19 were assessed in this single-center retrospective study. 189 patients, whose diagnosis was confirmed using real-time PCR, were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…In a case report, QTc prolongation was observed on the 9th day of treatment in a patient who was using favipiravir for Ebola virus infection 21 . However, small study by Cap et al in COVID‐19 patients showed no significant increase in QTc interval 22 . Together, available data indicate that favipiravir is better tolerated in terms of cardiac arrhythmia in COVID‐19 patients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a case report, QTc prolongation was observed on the 9th day of treatment in a patient who was using favipiravir for Ebola virus infection 21 . However, small study by Cap et al in COVID‐19 patients showed no significant increase in QTc interval 22 . Together, available data indicate that favipiravir is better tolerated in terms of cardiac arrhythmia in COVID‐19 patients.…”
Section: Discussionmentioning
confidence: 97%
“…21 However, small study by Cap et al in COVID-19 patients showed no significant increase in QTc interval. 22 Together, available data indicate that favipiravir is better tolerated in terms of cardiac arrhythmia in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 98%
“… 26 , 27 Also, Çap et al reported that in the ECG recordings received in the following days after the treatment was started in COVID-19 patients, there was a significant prolongation in the QT interval with HCQ, but there was no significant change with FPV. 28 Moreover, the effect of FPV on the QT interval in healthy adults was evaluated in a small-scale study (56 participants) in Japan. Patients were randomly assigned to receive 1200 mg FPV, 2400 mg FPV, moxifloxacin, or a placebo.…”
Section: Discussionmentioning
confidence: 99%
“…Fridericia formula is a formula recommended by the U.S. Food and Drug Administration (FDA) for clinical trials on drug safety. Fridericia formula calculation is QTc = QT/[R - R]1/3 [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%